Chronotherapy and intervertebral disc degeneration: understanding the role of circadian rhythm in degenerative processes - Zhang, Cong; Zhang, Rende; Zhao, Guanghai; Wu, Zuolong; Song, Wei; Ran, Rui; Zhou, Kaisheng; Zhang, Haihong (Frontiers in Cell and Developmental Biology, 2025)
Intervertebral disc degeneration (IDD) and low back pain are prevalent issues globally, affecting a significant portion of the adult population. Recent research has highlighted the crucial role of circadian rhythms in the degenerative processes of intervertebral discs (IVDs). Circadian rhythms are regulated by a coordinated network of oscillators, consisting of a central clock system and various peripheral clock systems. These rhythms are influenced by environmental factors, particularly the light/dark cycle, and disruptions can lead to cumulative stress and imbalances within the body. The IVD tissue contains an autonomous oscillating peripheral clock, and evidence suggests that disruptions in these circadian rhythms can accelerate tissue aging and increase the risk of IDD. Studies have shown that reduced expression of clock genes, such as BMAL1, is an independent risk factor for IDD progression. Furthermore, circadian disruptions can imbalance anabolic and catabolic processes within IVDs, leading to tissue degeneration. Understanding the role of circadian rhythms in IDD may provide valuable insights into potential therapeutic strategies for preventing or mitigating disc degeneration. The review explores the entrainment of circadian rhythms with external physiological signals and their impact on disc physiology. Notably, disruptions in circadian rhythms have been linked to accelerated disc degeneration, with implications for tissue aging, metabolic imbalances, and inflammatory responses. Furthermore, the paper discusses potential therapeutic strategies, including chronotherapy, which aims to synchronize treatment interventions with circadian rhythms to optimize outcomes in IDD management. Understanding the intricate interplay between circadian rhythms and IDD could pave the way for innovative treatment approaches, ultimately improving patient care.